Effect of organic sources of minerals on fat-corrected milk yield of dairy cows in confinement - Del Valle, Tiago Antonio; Jesus, Elmeson Ferreira de; Paiva, Pablo Gomes de; Bettero, Vitor Pereira; Zanferari, Filipe; Acedo, Tiago Sabella [UNESP]; Monteiro Tamassia, Luis Fernando [UNESP]; Renno, Francisco Palma (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2015)
This study evaluated the effects of organic and inorganic sources of minerals in diets for mid-lactation dairy cows on milk yield and composition, intake and total apparent digestibility of dry matter and nutrients, blood parameters, microbial protein synthesis, and energy and protein balances. Twenty Holstein cows averaging 146.83 +/- 67.34 days in milk and weighing 625.30 +/- 80.37 kg were used. The experimental design was a crossover. Diets were composed of corn silage (50%), ground grain corn, and soybean meal, differing with regard to the sources of trace minerals, plus an organic and inorganic mix. The organic mineral source increased milk fat and fat-corrected milk yield without changing milk yield, intake, or total apparent digestibility. Blood parameters, microbial protein synthesis, and energy and protein balances were not affected by the sources of minerals. Organic sources of minerals improve milk fat yield without affecting other parameters.
Keywords: Holstein; Milk fat; Mineral nutrition; Organic mineral